Immunomodulatory properties of tualang honey on BALB/c mice - Kit, Tan Tiong (Universiti Sains Malaysia, 2013)
Local natural product extracts has been gaining great focus from research and therapeutic aspect. Similarly, the outcome of studies on one of nation’s renowned honey Tualang (TH) (Koompassia excelsa) has profoundly anchored its board aptitude in anti-inflammatory, anti-oxidant and anti-microbial properties. This research focuses on the study of the immunomodulatory properties of TH in BALB/c. TH was orally administered daily for 14 days to BALB/c male mice (5/group) in dose ranging from 0.5 g/kg, 1.5 g/kg and 3.0 g/kg namely Low group, Medium group and High group. Pre-treatment and post-treatment body weights were measured. Upon sacrificing, the spleen was weighed and then homogenized. The splenocytes were stained with various surface markers antibodies namely CD3+/CD4+(T helper), CD3+/CD8+(T cytotoxic), CD14+ (macrophage) and CD19+ (B lymphocyte) and immune cell populations were obtained by using flow cytometer. On the other hand, proliferation assay of splenocytes were done by using CellTiter 96® AQueous One Solution Cell Proliferation Assay (MTS). Body weight in Control, Medium and High groups showed increment after the treatment but body weight of mice in Low group decreased upon completion of TH treatment. BALB/c mice treated with TH showed increased populations of CD3+/CD4+, CD3+/CD8+, CD14+ and CD19+ compared to control group. Proliferation analysis of splenocytes as well as spleen weight obtained from TH-treated mice also showed an increment. The results revealed the immunostimulant potential of TH in mice by enhancing lymphocyte populations especially T helper (CD3+/CD4+), cytotoxic (CD3+/CD8+) and B (CD19+) cells.